Pengaruh Rotasi Jabatan dan Pelatihan Pegawai Terhadap Kinerja Penyuluh Pertanian Lapangan dengan Kompetensi Penyuluh Pertanian Lapangan Sebagai Variabel Intervening Studi pada Dinas Pertanian Kabupaten Pati - Ida Sudarti; Kertati Sumekar; Supriyono Supriyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of job rotation and employee training on the performance of field agricultural extension workers with the competence of field agricultural extension workers as an intervening variable. This study uses primary data in the form of questionnaires. The sampling method used purposive sampling and obtained a sample of 105 respondents. Data analysis used in this study is a structural equation model. The results of this study state that job rotation has a positive and significant effect on the competence of agricultural extension workers, employee training has a positive and significant effect on the competence of agricultural extension workers, job rotation has a positive and significant effect on the performance of agricultural extension workers, employee training has no significant effect on the performance of agricultural extension workers, and agricultural extension competence has a positive and significant effect on the performance of agricultural extension workers.